2019
DOI: 10.1002/brb3.1340
|View full text |Cite
|
Sign up to set email alerts
|

Oral supplementation with ginseng polysaccharide promotes food intake in mice

Abstract: Introduction Ginseng polysaccharide (GPS, same as Panax polysaccharide) is a kind of polysaccharide extracted from ginseng. It has been reported that GPS has the ability to activate innate immunity, regulates blood sugar balance, and improves antioxidant capacity, but the effect on feeding behavior and its mechanism remains unclear. Method To investigate the possible effect of GPS on feeding behavior of animals, mice were supplied with GPS in water, and food intake, hedonic feeding behavior, anxiety‐like behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Other alternatives include addition of biological and functional additives to the diet, such as moringa, mulberry, Chinese herbal medicine, tea polyphenol, dietary fiber, and ginseng polysaccharides. Among them, ginseng polysaccharides, due to their high content of polysaccharides, peptides, saponins, and other active substances, can be used as functional feed additives to promote food intake [8], improve immunity [9], and decrease the amount of abdominal fat and serum cholesterol [10] in broilers. Therefore, if ginseng polysaccharide is mixed with microbially fermented feed, it may have a positive impact on the development of new alternative antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Other alternatives include addition of biological and functional additives to the diet, such as moringa, mulberry, Chinese herbal medicine, tea polyphenol, dietary fiber, and ginseng polysaccharides. Among them, ginseng polysaccharides, due to their high content of polysaccharides, peptides, saponins, and other active substances, can be used as functional feed additives to promote food intake [8], improve immunity [9], and decrease the amount of abdominal fat and serum cholesterol [10] in broilers. Therefore, if ginseng polysaccharide is mixed with microbially fermented feed, it may have a positive impact on the development of new alternative antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The assumption of campesterol, β-elemene, ginsenoside Rb1, contained in P. ginseng have been related to modulation of neuropeptide genes that regulate energy balance and food intake. The analysis of data suggests that P.gineng can regulate neuropeptides associated with appetite [ 120 , 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is reported that neutral ginseng polysaccharides can reduce inflammation by inhibiting inflammatory-related mediator (NO) and cytokines (TNF-α, IL-6, and IL-1β) release [ 18 ]. Oxidative stress and dopamine signaling are also involved in the mechanisms mediated of GP [ 27 ]. Noticeably, GP can not only exert directly pharmacological effect on human body, but also exert indirect effect, that is, promoting the absorption of saponins.…”
Section: Bioactivitiesmentioning
confidence: 99%
“…Chen et al [ 69 ] conducted experiments in vitro about the scavenging ability of GP on DPPH free radicals, superoxide anion radicals and hydroxyl radicals. The results showed that it had appreciable scavenging ability to these three free radicals and showed dose dependence in a certain concentration range [ 27 ]. Due to the existence of dose-effect relationship, researchers compared the content of GP in above-ground and under-ground and found the latter is higher.…”
Section: Effects Of Ginseng Polysaccharides In Nervous System Diseasementioning
confidence: 99%